2020
DOI: 10.15537/smj.2020.3.24909
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of obsessive-compulsive disorder comorbidity and obsessive-compulsive symptom dimensions in patients with schizophrenia

Abstract: To assess obsessive-compulsive disorder (OCD) comorbidity and obsessive-compulsive symptom (OCS) dimensions in patients with schizophrenia. Methods: This cross-sectional study included 300 patients with schizophrenia who were applied to the to the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
(68 reference statements)
1
4
0
Order By: Relevance
“…As regard gender, in the present study 52% of patients were male and 48% were females. This finding is in line with the study by Kruger et al, [8] but in contrast to the study by and Kokurcan and Safak [9] in which there was preponderance of men.…”
Section: Discussionsupporting
confidence: 91%
“…As regard gender, in the present study 52% of patients were male and 48% were females. This finding is in line with the study by Kruger et al, [8] but in contrast to the study by and Kokurcan and Safak [9] in which there was preponderance of men.…”
Section: Discussionsupporting
confidence: 91%
“…[3][4][5] Despite the relatively low prevalence, schizophrenia is associated with substantial health, societal, and economic burden, including high healthcare resource utilization [6][7][8] and increased risk of premature mortality, disability, mental health comorbidities, and suicide. [9][10][11][12][13][14][15] Furthermore, the difficult symptoms associated with schizophrenia profoundly decrease patients' quality of life and daily functioning. 16,17 As a result of confirmed cases of illness caused by a SARS-CoV-2 Novel Coronavirus (2019-nCoV or COVID- 19), the US Secretary of Health and Human Services determined the existence of a public health emergency on January 27, 2020.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the first psychotic symptoms started earlier in the schizo-obsessive group when compared with schizo-obsessive patients and another group of patients with schizophrenia who did not have appropriate OCS in terms of age, sex, and hospitalization (O'Connell et al, 2018). In addition, there was no difference between schizo-obsessive patients and patients with schizophrenia without OCS/OCD in terms of positive, negative, and disorganized schizophrenia symptoms (Kokurcan and Şafak, 2020). Again, in a study comparing the schizo-obsessive patient group and the OCD patient group in terms of clinical and demographic characteristics, it was shown that there was no difference between the two groups in terms of the frequency and severity of OCS (Kazhungil et al, 2017).…”
mentioning
confidence: 96%